Humiliation, degradation, dehumanization human dignity violated - Kaufmann, Paulus; Kuch, Hannes 1978-; Neuhaeuser, Christian; Webster, Elaine; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Degradation, dehumanization, instrumentalization, humiliation, and nonrecognition ? these concepts point to ways in which we understand human beings to be violated in their dignity. Violations of human dignity are brought about by concrete practices and conditions; some commonly acknowledged, such as torture and rape, and others more contested, such as poverty and exclusion. This volume collates reflections on such concepts and a range of practices, deepening our understanding of human dignity and its violation, bringing to the surface interrelationships and commonalities, and pointing to the values that are thereby shown to be in danger. In presenting a streamlined discussion from a negative perspective, complemented by conclusions for a positive account of human dignity, the book is at once a contribution to the body of literature on what dignity is and how it should be protected as well as constituting an alternative, fresh and focused perspective relevant to this significant recurring debate. As the concept of human dignity itself crosses disciplinary boundaries, this is mirrored in the unique range of perspectives brought by the book's European and American contributors ? in philosophy and ethics, law, human rights, literature, cultural studies and interdisciplinary research. This volume will be of interest to social and moral philosophers, legal and human rights theorists, practitioners and students
Foreword Manfred Nowak Human Dignity Violated: A Negative Approach Paulus Kaufmann, Hannes Kuch, Christian Neuhäuser and Elaine Webster Three Crucial Turns on the Road to an Adequate Understanding of Human Dignity Ralf Stoecker Part 1: Conceptions and Theories Humiliation: The Collective Dimension Christian Neuhäuser The Rituality of Humiliation: Exploring Symbolic Vulnerability Hannes Kuch Instrumentalization: What does it Mean to Use a Person? Paulus Kaufmann Degradation: A Human Rights Law Perspective Elaine Webster Dehumanization: Perceiving the Body as (In)Human Sophie Oliver Part 2: Practices of Violating Human Dignity Torture: How Denying Moral Standing Violates Human Dignity Andreas Maier Rape: Does International Human Rights Law Adequately Protect the Dignity of Women? Ivana Radacic Social Exclusion: Practices of Misrecognition Steffen K. Herrmann Absolute Poverty: Human Dignity, Self-Respect, and Dependency Peter Schaber Relative Poverty: On a Social Dimension of Dignity Julia Müller and Christian Neuhäuser Trade Exploitation: Crossing the Threshold between Acceptable and Unacceptable Labor Conditions Kirsteen Shields Bonded Labour: Dynamics Between Bondage, Identity and Dignity Tamara Enhuber Part 3: Conclusions for a Positive Account of Human Dignity Human Dignity and Human Rights Marcus Düwell Dignity and Preservation of Personhood Samuel Kerstein 15. Embodied Self-Respect and the Fragility of Human Dignity: A Human Rights Approach Arndt Pollmann Index
Includes bibliographical references and index
Electronic reproduction
Keywords: Human rights; Respect for persons; Dignity